Bringing the Arts into the Library - Smallwood, Carol, 1939- (ALA Editions, 2014)
Is your library so engaged in keeping current with technology that it has overlooked bringing the arts into the community? Collaboration with community arts organizations can be a key factor in the success of cultural programming in libraries. Learn about noteworthy and successful programs serving diverse communities and populations, to get ideas for your own environment.